2018
DOI: 10.1016/j.bios.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

An integrated portable system for single chip simultaneous measurement of multiple disease associated metabolites

Abstract: Metabolites, the small molecules that underpin life, can act as indicators of the physiological state of the body when their abundance varies, offering routes to diagnosis of many diseases. The ability to assay for multiple metabolites simultaneously will underpin a new generation of precision diagnostic tools. Here, we report the development of a handheld device based on complementary metal oxide semiconductor (CMOS) technology with multiple isolated micro-well reaction zones and integrated optical sensing al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…SPR measurements have also been demonstrated on the same platform in related works [28,29]. Multimode multiplexing and simultaneous assays have also been achieved [32,35,36]. Altogether, the chip demonstrated to be suitable for four different sensing techniques to be used independently or simultaneously.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…SPR measurements have also been demonstrated on the same platform in related works [28,29]. Multimode multiplexing and simultaneous assays have also been achieved [32,35,36]. Altogether, the chip demonstrated to be suitable for four different sensing techniques to be used independently or simultaneously.…”
Section: Discussionmentioning
confidence: 85%
“…In [35], we demonstrated that the Multicorder platform can operate both colorimetric and pH sensing to simultaneously quantify glucose and cholesterol. In [32], we also demonstrate that physical separations fabricated on top of the sensing area enable the use of the Multicorder for simultaneous enzymebased assays of multiple metabolites. Multiplexing immunoassays on the top of the Multicorder chip have also been demonstrated [36].…”
Section: Dmentioning
confidence: 81%
See 1 more Smart Citation
“…Handheld engineering solutions are now capable of sampling organic metabolites. Microchip technology allows multiple metabolite analysis and a coded result with the potential for robust, affordable and non-invasive testing [ 49 ]. In OA, these technologies could enable cost-effective early detection in asymptomatic individuals and sub-stratification in symptomatic individuals.…”
Section: “Personalised Medicine” and The Impact Of Metabolic Profilinmentioning
confidence: 99%
“…The expanding capabilities of these sensors require faster and more complex sensing platforms, able to address each sensing spot individually. Traditional optical setups consisting of an optical source and a spectrum analyzer are being replaced with digital cameras that record all signals simultaneously or scanners that interrogate each transducer sequentially [34][35][36]. Some other solutions include multiple wavelength interrogation or exploiting plasmonic and fluorescent properties [37,38].…”
Section: Introductionmentioning
confidence: 99%